Prognostic Factors in Severe Chagasic Heart Failure - Costa,Sandra de Araújo (2017)
Abstract Background: Prognostic factors are extensively studied in heart failure; however, their role in severe Chagasic heart failure have not been established. Objectives: To identify the association of clinical and laboratory factors with the prognosis of severe Chagasic heart failure, as well as the association of these factors with mortality and survival in a 7.5-year follow-up. Methods: 60 patients with severe Chagasic heart failure were evaluated regarding the following variables: age, blood pressure, ejection fraction, serum sodium, creatinine, 6-minute walk test, non-sustained ventricular tachycardia, QRS width, indexed left atrial volume, and functional class. Results: 53 (88.3%) patients died during follow-up, and 7 (11.7%) remained alive. Cumulative overall survival probability was approximately 11%. Non-sustained ventricular tachycardia (HR = 2.11; 95% CI: 1.04 - 4.31; p<0.05) and indexed left atrial volume ≥ 72 mL/m2 (HR = 3.51; 95% CI: 1.63 - 7.52; p<0.05) were the only variables that remained as independent predictors of mortality. Conclusions: The presence of non-sustained ventricular tachycardia on Holter and indexed left atrial volume > 72 mL/m2 are independent predictors of mortality in severe Chagasic heart failure, with cumulative survival probability of only 11% in 7.5 years.